A comparison of the efficacy and tolerability of three corticosteroid treatment regimens in patients with alopecia areata. (17th February 2022) - Suchonwanit, Poonkiat; Kositkuljorn, Chaninan; Mahasaksiri, Tippapai; Leerunyakul, Kanchana
Abstract: Background: Topical corticosteroids (TC) and/or intralesional corticosteroids (IC) are considered first-line treatments for patch-type alopecia areata (AA). However, the efficacies of TC monotherapy, IC monotherapy, and combined topical and intralesional corticosteroids (CC) in patients with AA have never been compared. Objective: To evaluate and compare the efficacy and tolerability of 3 corticosteroid treatments (TC, IC, and CC) in patients with AA. Methods: A study of patients with AA who received TC, IC, or CC was conducted. Outcomes including initial hair regrowth (25% regrowth), significant hair regrowth (>80% regrowth), and adverse events were statistically compared. Cox proportional hazards regression analysis was used to identify factors that influence the treatment response. Results: One hundred and forty-eight patients were eligible for analysis. The response rates of initial and significant hair regrowth were comparable among 3 treatment groups. Multivariate analysis revealed that an AA treatment duration of longer than 6 months was associated with a lower probability of significant hair regrowth. A small proportion of patients experienced adverse effects. Conclusion: The 3 corticosteroid treatment regimens are effective, safe, and show no significant differences in treatment outcomes. However, an AA duration longer than 6 months portends a lack of significant hair regrowth.